2015
DOI: 10.1007/s10620-015-3561-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein A4 Controls Cell Migration and Gastric Ulcer Healing

Abstract: HSPA4 regulates the expression of SDF-1 and Twist in fibroblasts, thereby controlling gastric ulcer healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Interestingly, Zebrafish HspA4 was also upregulated in the intestinal epithelium within the gut under inflammatory stress conditions ( 169 ). Using HspA4-deficient mice and human tissue samples, Sakurai et al showed that the expression of HspA4 was inversely correlated to gastric ulcer healing induced by endoscopic submucosal resection ( 170 ). Further studies revealed that HspA4 downregulated the expression of stromal cell-derived factor 1 (SDF-1, also known as CXCL12), which signals through its cognate receptor CXC chemokine receptor 4 (CXCR4).…”
Section: Large Hsps and Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Zebrafish HspA4 was also upregulated in the intestinal epithelium within the gut under inflammatory stress conditions ( 169 ). Using HspA4-deficient mice and human tissue samples, Sakurai et al showed that the expression of HspA4 was inversely correlated to gastric ulcer healing induced by endoscopic submucosal resection ( 170 ). Further studies revealed that HspA4 downregulated the expression of stromal cell-derived factor 1 (SDF-1, also known as CXCL12), which signals through its cognate receptor CXC chemokine receptor 4 (CXCR4).…”
Section: Large Hsps and Inflammatory Diseasesmentioning
confidence: 99%
“…Further studies revealed that HspA4 downregulated the expression of stromal cell-derived factor 1 (SDF-1, also known as CXCL12), which signals through its cognate receptor CXC chemokine receptor 4 (CXCR4). The resultant inhibition of cell migration delayed gastric ulcer healing ( 170 ).…”
Section: Large Hsps and Inflammatory Diseasesmentioning
confidence: 99%
“…The 110 kDa heat shock protein (Hsp110) family, including Hsp105, Apg1, and Apg2, are cytosolic chaperones that belong to the Hsp70 superfamily [ 6 10 ]. In addition to serving housekeeping roles during protein homeostasis, this protein family has been linked to wide ranging cellular processes including cell migration [ 11 ], spindle length control [ 12 ], and molecular scaffolding [ 13 ]. Importantly, as the Hsp110 family has also been implicated in many protein misfolding diseases, such as amyotrophic lateral sclerosis [ 14 , 15 ], prion disease [ 16 ], Alzheimer’s disease [ 17 ], cystic fibrosis [ 18 ], and polyglutamine disease [ 19 , 20 ], clarifying its precise mechanism of action in cells is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time qPCR and immunohistochemistry were previously described [13][14][15][16] . The following antibodies were used: anti-Bmi1, anti-CD3, anti-CD20, and anti-CD68 (Dako, Santa Clara, CA, USA).…”
Section: Biochemical and Immunochemical Analysesmentioning
confidence: 99%